2014
DOI: 10.1186/gb-2014-15-2-r24
|View full text |Cite
|
Sign up to set email alerts
|

Aging of blood can be tracked by DNA methylation changes at just three CpG sites

Abstract: BackgroundHuman aging is associated with DNA methylation changes at specific sites in the genome. These epigenetic modifications may be used to track donor age for forensic analysis or to estimate biological age.ResultsWe perform a comprehensive analysis of methylation profiles to narrow down 102 age-related CpG sites in blood. We demonstrate that most of these age-associated methylation changes are reversed in induced pluripotent stem cells (iPSCs). Methylation levels at three age-related CpGs - located in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
842
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 745 publications
(896 citation statements)
references
References 59 publications
27
842
2
8
Order By: Relevance
“…Studies that examined this period of human development have reported that DNA methylation levels increase rapidly and then stabilize by adulthood in both brain and blood (Alisch et al ., 2012; Lister et al ., 2013). From adulthood to advanced age, overall levels of DNA methylation remain stable in blood, while interindividual variability increases over that time (Talens et al ., 2012; Weidner et al ., 2014). Postadulthood, many studies have found a mean decrease in blood DNA methylation with increasing age (Bjornsson et al ., 2004; Boks et al ., 2009; Heyn et al ., 2012; Horvath et al ., 2012; Hannum et al ., 2013; Johansson et al ., 2013; Florath et al ., 2014; Weidner et al ., 2014).…”
Section: Dna Methylation Dynamics During Agingmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies that examined this period of human development have reported that DNA methylation levels increase rapidly and then stabilize by adulthood in both brain and blood (Alisch et al ., 2012; Lister et al ., 2013). From adulthood to advanced age, overall levels of DNA methylation remain stable in blood, while interindividual variability increases over that time (Talens et al ., 2012; Weidner et al ., 2014). Postadulthood, many studies have found a mean decrease in blood DNA methylation with increasing age (Bjornsson et al ., 2004; Boks et al ., 2009; Heyn et al ., 2012; Horvath et al ., 2012; Hannum et al ., 2013; Johansson et al ., 2013; Florath et al ., 2014; Weidner et al ., 2014).…”
Section: Dna Methylation Dynamics During Agingmentioning
confidence: 99%
“…From adulthood to advanced age, overall levels of DNA methylation remain stable in blood, while interindividual variability increases over that time (Talens et al ., 2012; Weidner et al ., 2014). Postadulthood, many studies have found a mean decrease in blood DNA methylation with increasing age (Bjornsson et al ., 2004; Boks et al ., 2009; Heyn et al ., 2012; Horvath et al ., 2012; Hannum et al ., 2013; Johansson et al ., 2013; Florath et al ., 2014; Weidner et al ., 2014). These changes are less likely to occur in promoters and more likely to be observed in enhancers (Johansson et al ., 2013).…”
Section: Dna Methylation Dynamics During Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…While the key features of epigenetic drift remain to be defined, several observations have been made that characterize age‐related methylation changes across human tissues. These include the hypermethylation of stem cell genes (Rakyan et al ., 2010; Teschendorff et al ., 2010), a general linear correlation between the methylation level of certain CpGs and the chronological age (Hannum et al ., 2013; Horvath, 2013; Weidner et al ., 2014), and the hypermethylation of CpG islands (Yuan et al ., 2015). The molecular and phenotypic consequences of these alterations remain a topic of active research.…”
Section: Introductionmentioning
confidence: 99%